Untargeted metabolomics of neuronal cell culture: A model system for the toxicity testing of insecticide chemical exposure. Issue 12 (6th July 2017) - Hayton, Sarah; Maker, Garth L.; Mullaney, Ian; Trengove, Robert D.
Abstract: Toxicity testing is essential for the protection of human health from exposure to toxic environmental chemicals. As traditional toxicity testing is carried out using animal models, mammalian cell culture models are becoming an increasingly attractive alternative to animal testing. Combining the use of mammalian cell culture models with screening‐style molecular profiling technologies, such as metabolomics, can uncover previously unknown biochemical bases of toxicity. We have used a mass spectrometry‐based untargeted metabolomics approach to characterize for the first time the changes in the metabolome of the B50 cell line, an immortalised rat neuronal cell line, following acute exposure to two known neurotoxic chemicals that are common environmental contaminants; the pyrethroid insecticide permethrin and the organophosphate insecticide malathion. B50 cells were exposed to either the dosing vehicle (methanol) or an acute dose of either permethrin or malathion for 6 and 24 hours. Intracellular metabolites were profiled by gas chromatography–mass spectrometry. Using principal components analysis, we selected the key metabolites whose abundance was altered by chemical exposure. By considering the major fold changes in abundance (>2.0 or <0.5 from control) across these metabolites, we were able to elucidate important cellular events associated with toxic exposure including disrupted energy metabolism and attempted protective mechanisms from excitotoxicity. Our findings illustrate the ability of mammalian cell culture metabolomics to detect finer metabolic effects of acute exposure to known toxic chemicals, and validate the need for further development of this process in the application of trace‐level dose and chronic toxicity studies, and toxicity testing of unknown chemicals. Abstract : The use of mammalian cell culture models combined with powerful molecular profiling techniques can uncover unknown biochemical bases of toxicity and provide an alternative to toxicity testing in animals. An untargeted metabolomics approach was used to characterize the metabolome of B50 rat neuronal cells, following exposure to two neurotoxic insecticides, permethrin and malathion. Cells were profiled by gas chromatography–mass spectrometry. A number of key intracellular metabolites were identified and important cellular events including energy metabolism were disrupted by chemical exposure.